2018
DOI: 10.3390/ijerph15112520
|View full text |Cite
|
Sign up to set email alerts
|

Development of a System Measurement Model of the Brazilian Hospital Accreditation System

Abstract: The purpose of this study is to develop and validate a measurement model that evaluates the Brazilian hospital accreditation methodology (ONA), based on a multivariate model using structural equation modeling (SEM). The information used to develop the model was obtained from a questionnaire sent to all organizations accredited by the ONA methodology. A model was built based on the data obtained and tested through a structural equation modeling (SEM) technique using the LISREL® software (Scientific Software Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…According to hospital administrators in Iran, decreasing the number of standards and criteria while increasing transparency may improve the accreditation process’s efficiency [ 29 ]. This finding was corroborated by a Brazilian study that identified leadership action as a key element in the certification process [ 30 ].…”
Section: Theoretical Backgroundsupporting
confidence: 56%
“…According to hospital administrators in Iran, decreasing the number of standards and criteria while increasing transparency may improve the accreditation process’s efficiency [ 29 ]. This finding was corroborated by a Brazilian study that identified leadership action as a key element in the certification process [ 30 ].…”
Section: Theoretical Backgroundsupporting
confidence: 56%
“…Cronbach’s α was 0.78 and its corrected total-item correlation was >0.50, indicating that the P-MFSMS reached acceptable reliability [ 29 , 30 , 31 ]. There are different reports about the acceptable values of α, ranging from 0.70 to 0.95, and a low α appears if the assumptions of the essentially tau-equivalent approach are not met, but a high value of α (≥0.90) may suggest redundancies and show that the test length can be shortened [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…They believed that the executive structure of the accreditation system plays a significant role in evaluating the accreditation of hospitals (28). Curia et al, in developing a model for measuring the accreditation system of Brazilian hospitals in 2019, found that leadership, staff management, quality management, organizational culture, process orientation, and safety are strongly related to the development of health organizations and can directly affect the accreditation process (29). In 2011, Al-Khanizan et al conducted a study on the impact of accreditation on the quality of health services and found that accreditation programs improve output indicators and clinical conditions, as well as specific accreditation programs that have a positive effect on specialized clinical processes.…”
Section: Discussionmentioning
confidence: 99%